Gambaran Pelaksanaan Protokol Covid-19 pada Civitas Fakultas Keperawatan Universitas Riau di Era New Normal - Erika; Dwi Apri Kurniawan; Rismadefi Woferst (HEALTH CARE : JURNAL KESEHATAN, 2021)
Abstract Introduction: The Covid-19 health protocol is a role that is carried out in accordance with established health regulatory standards in order to prevent the Covid-19 pandemic. The Covid-19 health protocol in educational settings includes washing hands, wearing masks, maintaining physical distance, avoiding crowds, and avoiding sharing personal tools and equipment. Method: This study employed a descriptive design aimed at describing the implementation of the health protocol of Covid-19. The research sample was the members of the Faculty of Nursing, the University of Riau who happened to be around the faculty with an accidental sampling technique totaling 100 people. The measuring instrument was in the form of an observation sheet. The obtained data were analyzed using univariate analysis. Results: 66 people (66%) did not wash their hands before entering the faculty area, 68 people (68%) did not wash their hands after visiting the faculty area. 95 people (95%) wore a mask, covering the nose, chin, and mouth while in the faculty area. All of them (100%) did not shake hands/ kiss/ hug when meeting with other members of the community. 97 people (97%) of them were not in groups in the faculty area. All of them left the faculty area immediately after completing their activities (100%). All of them (100%) also did not share personal food or drinks. Almost all of them (99%) did not borrow stationery, books, and other personal equipment. Conclusion: The implementation of the health protocol of the Covid-19 in the Faculty of Nursing at the University of Riau in the New Normal Era has been quite good. However, the health protocol has not been optimal in the implementation of washing hands before and after visiting the faculty area. Suggestion: The results of this study are expected to become a reference for the application or implementation of the Covid-19 protocol in the scope of nursing education